Factors Affecting Interest in Accounting Students As Public Accountants (Empirical Study at Indo Global Mandiri University) - Vira Adela; Harsi Romli; Andini Utari Putri (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to investigate the factors that influence the interest of accounting students to become public accountants (empirical study at Universitas Indo Global Mandiri, 2017-2019). The data used in this study are primary data collected through questionnaires. Sampling using a purposive sampling technique obtained 69 respondents. The research method used is simple linear regression analysis. The research results prove that attitudes, subjective norms, and control over behavior had a significant effect on the interest variable of accounting students as public accountants. Furthermore, the results evince that simultaneously attitudes, subjective norms, and control over behavior had a significant effect on the student interest variable to become public accountants